Relationship Between the Organizational Change and Organizational Cynicism: A Research in Denizli Organized Industrial Zone - Aytas, Seher; Barutcu, Esin (European Scientific Journal, ESJ, 2017)
The aim of this study is to measure whether the workers have relevant feelings of distrust and skepticism of individuals for their organizations as a result cynicism in the environment of change and if it exists to measure of this relation’s level and direction. The research was conducted on a total of 100 white-collar workers who are working in the enterprises operating in Denizli Organized Industrial Zone by survey method. The data obtained from the survey methodology was subjected to a variety of statistical analyses. Significant differences has emerged when examining the relationships of employees of organizations with cynicism based on the changes in the organizations, personality cynicism, cynicism focuses on trust in organizations and management trust, and cynicism in organizations.